Prospective Comparison of Conventional External Dacryocystorhinostomy and Endonasal Laser Dacryocystorhinostomy (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Background:Epiphora, a common manifestation of chronic dacryocystitis, requires definitive treatment through dacryocystorhinostomy (DCR), a surgical procedure aimed at creating an alternative fluid drainage pathway.This study aimed to assess how effective both external dacryocystorhinostomy (Ex-DCR) and  endonasal dacryocystorhinostomy (Endo-DCR) are in managing chronic dacryocystitis, with a specific focus on surgical duration, complication rates, and treatment outcomes.Methods: In this study, sixty participants were prospectively enrolled and evenly divided into two groups. Thirty patients were assigned to the first group and underwent En-DCR surgery, while the second group, also comprising thirty patients, underwent Ex-DCR surgery. Both groups were monitored for a duration of 9 months and assessed for surgical duration, perioperative and postoperative complications, and eventual surgical outcomes.Results: The distribution of patients across age groups and sexes was similar between the two groups (p>0.05). Clinical features such as epiphora, epiphora with discharge, and epiphora with swelling were comparable between groups. En-DCR group demonstrated significantly less intraoperative bleeding (mean:13.5 ml vs 50 ml; p